2019
DOI: 10.3389/fevo.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Change as a Driver of Bottom-Up and Top-Down Factors in Agricultural Landscapes and the Fate of Host-Parasitoid Interactions

Abstract: The global climate is rapidly changing and the evidence is increasingly manifesting across various biological systems. For arthropods, several studies have demonstrated how changing climates affect their distribution through phenological and physiological responses, largely focusing on various organismal fitness parameters. However, the net-effect of the changing climate among ecological communities may be mediated by the feedback pathways among interacting trophic groups under environmental change. For agroec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 165 publications
(223 reference statements)
0
52
0
Order By: Relevance
“…This will allow for a more effective assessment of constraints of biological control associated with thermal stress prior to organismal loss of physiological function, e.g. through thermal performance curves (see discussions in [ 37 ]). While CTLs are only a measure of the fate of an organism at extreme temperatures [ 92 , 93 ], they can still be useful in predictive models associated with population dynamics [ 27 , 37 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will allow for a more effective assessment of constraints of biological control associated with thermal stress prior to organismal loss of physiological function, e.g. through thermal performance curves (see discussions in [ 37 ]). While CTLs are only a measure of the fate of an organism at extreme temperatures [ 92 , 93 ], they can still be useful in predictive models associated with population dynamics [ 27 , 37 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thermal performance is highly enigmatic and varies among species, ontogeny, age [ 36 ] and size [ 29 ]. Moreover, natural enemy efficacy also depends on the fate of bottom-up and top-down effects, which have been reported to favour pest and vector species [ 37 ]. As such, even slight alterations to temperature can compromise or heighten species fitness, community interactions and structure [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, these effects will hinder IPM tactics ( Oerke 2006 , Maino et al 2017 , Taylor et al 2018 , Matzrafi 2019 ). GCC will have a negative impact on biological control, causing asynchrony between hosts and parasitoids, while lowering the efficacy of pesticide-free management techniques ( Chidawanyika et al 2019 ). Phenology changes and environmental cues altered by GCC will create plant–pollinator mismatch, ultimately reducing the production of seed and fruit commodities ( Forrest 2015 ).…”
Section: Debates Introductionmentioning
confidence: 99%
“…Intrinsic mechanisms refer to direct effects of climate-associated abiotic parameters on an organism (Cornelissen 2011;Robinet & Roques 2010). Extrinsic mechanisms refer to indirect effects, mediated for instance through shifted distributions, altered phenology or physiology of lower trophic levels (Han et al 2019;Kaplan et al 2016;Kharouba et al 2018;Jeffs & Lewis 2013;Pincebourde et al 2017;Chidawanyika et al 2019;Damien & Tougeron 2019;Renner & Zohner 2018). While investigating indirect effects of climate change across trophic levels is crucial to predict community shifts (van der Putten et al 2010), understanding the direct impact of climate change onto each trophic level is essential to characterize the underlying mechanisms (Thomson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature was identified as a key determinant of parasitoid developmental rates, survival, fecundity, parasitism and dispersal (Hance et al 2007;Walther et al 2002;Selvaraj et al 2013). Thermal performance curves revealed that increasing temperatures enhance parasitism success until a maximum at optimum temperature, beyond which any increase in temperature leads to a decline of parasitism success (Furlong & Zalucki 2017;Chidawanyika et al 2019). Optimum temperature was repeatedly reported to be lower for parasitoids than for their hosts, indicating that parasitoids may be more susceptible to elevated temperature than herbivores, resulting in lowered biocontrol efficacy over time (Furlong & Zalucki 2017).…”
Section: Introductionmentioning
confidence: 99%